Mindfulness-Based Interventions for the Treatment of Substance and Behavioral Addictions: A Systematic Review - Sancho, Marta; De Gracia, Marta; Rodríguez, Rita C.; Mallorquí-Bagué, Núria; Sánchez-González, Jéssica; Trujols, Joan; Sánchez, Isabel; Jiménez-Murcia, Susana; Menchón, Jose M. (Frontiers in Psychiatry, 2018)
Background Emotion (dys)regulation as well as the interventions for improving these difficulties are receiving a growing attention in the literature. The aim of the present paper was to conduct a systematic review about the efficacy of mindfulness-based interventions (MBIs) in both substance and behavioral addictions (BAs). Method A literature search was conducted using Cochrane, PubMed, and Web of Science. Fifty-four randomized controlled trials published in English since 2009 to April 2017 were included into a narrative synthesis. Results Mindfulness-based interventions were applied in a wide range of addictions, including substance use disorders (from smoking to alcohol, among others) and BAs (namely, gambling disorder). These treatments were successful for reducing dependence, craving, and other addiction-related symptoms by also improving mood state and emotion dysregulation. The most commonly used MBI approaches were as follows: Mindfulness-Based Relapse Prevention, Mindfulness Training for Smokers, or Mindfulness-Oriented Recovery Enhancement, and the most frequent control group in the included studies was Treatment as Usual (TAU). The most effective approach was the combination of MBIs with TAU or other active treatments. However, there is a lack of studies showing the maintenance of the effect over time. Therefore, studies with longer follow-ups are needed. Conclusion The revised literature shows support for the effectiveness of the MBIs. Future research should focus on longer follow-up assessments as well as on adolescence and young population, as they are a vulnerable population for developing problems associated with alcohol, drugs, or other addictions.